Educational Use of Social Media in Higher Education: Gender and Social Networking Sites as the Predictors of Consuming, Creating, and Sharing Content - Torun Emel Dikbaş (Sciendo, 2020)
Introduction:This study investigates the influence of gender and social networking sites (SNSs) such as Instagram, YouTube, WhatsApp, Facebook, and Twitter on consuming, creating, and sharing content within the educational social media usage behaviors of higher education students. The survey method is applied to measure students' social media usage for educational purposes. So that a more effective use of social media in education can be provided, it is important to understand how university students vary in their educational use of social media. The aim of this study is to examine how higher education students use social media for their educational purposes based on the content and activities with which the students engage. The aim of the research is to determine the correlations, if any, between gender, preferred SNS type, and educational social media in regard to consuming, creating and sharing content.